To add the given equations in the system:
-
First equation: \[ -6x + 4y = -8 \]
-
Second equation: \[ 6x - 12y = 14 \]
Now, let's add the two equations together:
\[ (-6x + 4y) + (6x - 12y) = -8 + 14 \]
Combine like terms:
- The \(x\) terms: \(-6x + 6x = 0\)
- The \(y\) terms: \(4y - 12y = -8y\)
- The constants: \(-8 + 14 = 6\)
So combining all of this, we get:
\[ 0x - 8y = 6 \]
This simplifies to:
\[ -8y = 6 \]
Thus, the correct equation that results from adding the two original equations is:
\[ -8y = 6 \]
So the answer is: Negative 8 y = 6.